Design of a web-based information system for domestic sea transportation services for limited liability company goods - Diki Pratama Putra; Army Trilidia Devega; Afrina Afrina (Journal of Computer-based Instructional Media, 2024)
This research aims to design and implement a web-based information system for domestic sea transportation services of goods owned by a Limited Liability Company. Currently, the Limited Liability Company faces challenges in administrating goods due to the time-consuming recording process and using Excel applications that are prone to manual errors, accompanied by inaccuracies due to the absence of an integrated database system. The information system developed uses the waterfall approach for system design and the Unified Modeling Language (UML) for modelling, resulting in a requirements analysis, UML-based system design, and eight database tables that support system functionality. The use of PHP programming and MySQL database in the system implementation resulted in a web application that allows PT NSE to manage administration in a timely and accurately, with reports stored in the database. To enhance the executive dashboard of the domestic sea transportation service information system for goods, revamping the display for more visual and informative data presentation is essential. Additionally, integrating an Excel export feature will facilitate further data processing by relevant parties. Adequate resources must be allocated to maintain and manage the system effectively, ensuring seamless and sustainable operation. By implementing this information system, the Limited Liability Company is expected to boost administrative efficiency and accuracy, thereby solidifying its position in Indonesia's logistics service industry.